2021
DOI: 10.1080/17597269.2021.1955585
|View full text |Cite
|
Sign up to set email alerts
|

Microwave subcritical water pre-treatment and enzymatic hydrolysis of geographical identification (GI) tag Indian black rice (Chakhao Poireiton) straw for fermentable sugar production

Abstract: Rice straw is an important feedstock for second-generation biorefineries, the majority being conventional white rice. This research investigated the potential of the straw of black rice Chakhao Poireiton, a rice variety of increasing importance, for biorefining. Pre-treatment of black rice straw was carried out in a pressurized microwave reactor and free sugar release was measured following digestion with Cellic® CTec3. This was compared to white rice straw. Pre-treatment (100 -200° C for 5 min) did not drasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The pH was 3.9, and the solution was acidic after the hydrothermal pretreatment because of the acid generated in situ by the RS under high-temperature conditions (Table 5b) [55]. The pH after microwave pretreatment was 6.4, indicating that temperature largely influenced the in situ acid formation during RS pretreatment as microwave pretreatment was performed at 100 • C, whereas hydrothermal pretreatment was conducted at 180 • C. Similar research reported by Moirangthem et al [36] indicated that when RS was pretreated using microwave radiation at 100 • C for 5 min, the pH value was 6.1, whereas at 180 • C for 5 min, the pH was 4.7. They reported a decrease in both the pH of the hydrolysate liquor and the recovered weight of the solid residue, along with subtle changes in the recovered RS residue.…”
Section: Comparison Of Rs and Pretreated Rs Residues And Solutions Pa...supporting
confidence: 77%
See 1 more Smart Citation
“…The pH was 3.9, and the solution was acidic after the hydrothermal pretreatment because of the acid generated in situ by the RS under high-temperature conditions (Table 5b) [55]. The pH after microwave pretreatment was 6.4, indicating that temperature largely influenced the in situ acid formation during RS pretreatment as microwave pretreatment was performed at 100 • C, whereas hydrothermal pretreatment was conducted at 180 • C. Similar research reported by Moirangthem et al [36] indicated that when RS was pretreated using microwave radiation at 100 • C for 5 min, the pH value was 6.1, whereas at 180 • C for 5 min, the pH was 4.7. They reported a decrease in both the pH of the hydrolysate liquor and the recovered weight of the solid residue, along with subtle changes in the recovered RS residue.…”
Section: Comparison Of Rs and Pretreated Rs Residues And Solutions Pa...supporting
confidence: 77%
“…Microwave pretreatment (MP) is a convenient and high-speed method. Microwave heat disrupts the waxy surface, degrades the lignin-hemicellulose complex, partially dissolving the lignin and hemicellulose in RS, which is beneficial for subsequent hydolyzation [36]. Cryocrushing pretreatment (CP) is a novel method of freezing materials and crushing them into powders using sub-zero temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Moirangthem et al pretreated rice straw pressurized microwave and digestion with enzymes. However, the rice straw require pretreatment above 160 °C for 5 min to obtain a significant impact on the subsequent zyme hydrolysis [23]. Compared with our study, biological pretreatment could occur der mild conditions but with a longer reaction time.…”
Section: Saccharification Based On Different Strategiesmentioning
confidence: 81%